Development of an Online Tool for Pasteurella multocida Genotyping and Genotypes of Pasteurella multocida From Different Hosts - Peng, Zhong; Liu, Junyang; Liang, Wan; Wang, Fei; Wang, Li; Wang, Xueying; Hua, Lin; Chen, Huanchun; Wilson, Brenda A.; Wang, Jia; Wu, Bin (Frontiers in Veterinary Science, 2021)
Pasteurella multocida is a versatile zoonotic pathogen. Multiple systems have been applied to type P. multocida from different diseases in different hosts. Recently, we found that assigning P. multocida strains by combining their capsular, lipopolysaccharide, and MLST genotypes (marked as capsular: lipopolysaccharide: MLST genotype) could help address the biological characteristics of P. multocida circulation in different hosts. However, there is still lack of a rapid and efficient tool to diagnose P. multocida according to this system. Here, we developed an intelligent genotyping platform PmGT for P. multocida strains according to their whole genome sequences using the web 2.0 technologies. By using PmGT, we determined capsular genotypes, LPS genotypes, and MLST genotypes as well as the main virulence factor genes (VFGs) of P. multocida isolates from different host species based on their whole genome sequences published on NCBI. The results revealed a closer association between the genotypes and pasteurellosis rather than between genotypes and host species. With the advent of high-quality, inexpensive DNA sequencing, PmGT represents a more efficient tool for P. multocida diagnosis in both epidemiological studies and clinical settings.